KEANEKARAGAMAN MAMALIA KECIL DI HUTAN LINDUNG GUNUNG LUMUT, KABUPATEN PASIR, KALIMANTAN TIMUR - Agustinus - Suyanto (ZOO INDONESIA, 2008)
Suyanto, A. 2008. Biodiversity of small mammals in Gunung Lumut protectedforest, Pasir District, East Kalimantan. Zoo Indonesia 17(1): 1-6. Survey on thesmall mammals biodiversity was conducted by trapping, mistnetting, harp trapping,and interview in the Protected Forest of Gunung Lumut, District of Pasir, EastKalimantan Province for three weeks on November-December 2005. The surveyresulted 110 specimens representing 18 species, and from the interview resultedadditional information of six species, bringing the total number of observed smallmammals was 20.5 % of the total small mammals known lived in Kalimantan. Fourspecies of small mammals were endemic to Kalimantan and three species wereprotected by Indonesian Law. The result of survey was expected to support thechange of status from protected forest to national park.